Choosing to Come Back: Second-Generation Egyptians Returning as Social Change Agents - Khalil, Hajar (AUC Knowledge Fountain, 2023)
Research has found that upon visiting their parents’ homeland, second-generation immigrants were able to gain a better understanding of where they came from, allowing them to reflect upon their own lives in respect to their family history (Marschall, 2017). Some researchers call this journey the ‘self-awakening’ or ‘searching-self’ journey (Christou, 2003). The aim of this research is to understand the process of second-generation Egyptians return journey to their parent(s)’ homeland in order to create social change. The two main questions posed are: 1) How do second-generation Egyptians construct their narrative identity, and 2) How do they conceptualize themselves as social change agents? The life narratives of four second-generation Egyptian returnees who decided to move to Egypt, their parent(s)’ homeland, and partake in social change are explored. Through their narratives it is possible to see the interplay of sociopolitical and historical factors, timing in life, and family, on their decision to move to Egypt, their identity formation, and their understanding of themselves as social change agents. These findings are discussed in terms of their childhood experiences in Egypt, their mothers’ experiences in Egypt, their encounters with their family in Egypt, their identity negotiations, agency, and sense of belonging.